The Effectivity of Prosta Glandin Synthetase Inhibitors and Spasmolytics in Treatment of Renal Colic - Yalçın, Orhan; Baydinç, Can; Semerciöz, Atilla; Yeni, Ercan (Kocaeli Üniversitesi, 1996)
Spasmolytics, narcotic analgesics, calcium antagonists and prostaglandin synthetase inhibitors (NSAI) are applied widely in treatment of renal colic. Amoung these drugs, NSAI drugs are believed to be more effective and safe. In this trial, we purposed to compare NSAI and spasmolytic drugs as for their effects and side effects in the patients with renal colic. We studied in two group and each group contained 20 patients. In the first group we applied diclofenac sodium intramuscularely which is a NSAI drug and in the second group hyoscine N butylbromide was applied intramuscularely which is a spasmolytic drug. The results was noted after 15, 30, 45 and 60 minutes. We found no statistically significant difference between two groups for drug effectivities, but we found that there was a statistically significant difference in the side effects between the groups. In conclusion, we thought that NSAID can be the first preference for the treatment of renal colic.

Renal kolik tedavisinde spazmolitikler, narkotik analjezikler, kalsiyum antagonistleri ve prostaglandin sentetaz inhibitörleri olan nonsteroid antiinflamatuar analjezikler (NSAI) yaygın olarak kullanılmaktadır. Bunlardan NSAI ilaçlar etkili ve güvenilir olarak kabul edilmektedirler. Bu çalışmamızda NSAI analjezikler ile spazmolitik ilaçları renal kolikli hastalarda etkinlikleri ve yan etkileri yönünden karşılaştırmayı amaçladık. Bunun için 20’şer olguluk iki grup oluşturduk. Birinci gruba NSAI bir ilaç olan diklofenak sodyum (Dic. Na), ikinci gruba ise spazmolitik bir ilaç olan hyoscine N. bütil bromid (HNBB)'i intramusküler olarak uyguladık. Enjeksiyondan sonra 15 , 30 , 45 ve 60 inci dakikalardaki sonuçları not ettik. İki grup arasında ilaçların etkinlikleri yönünden istatistiksel olarak anlamlı fark olmamasına rağmen yan etkiler yönünden fark anlamlı idi. Buna göre; renal, üreteral kolikli hastaların tedavisinde NSAI’ların öncelikle tercih edilebilir olduğu sonucuna vardık.
Prostaglandin Sentetaz İnhibitörleri ile Spazmolitiklerin Renal Kolik Tedavisindeki Etkinlikleri
Keywords: Urology; Üroloji